Gelsolin-mediated actin filament severing, mechanics, and conformational changes at neutral and acidic pH - Douglas, Taylor V.; Toland, Claire A.; Paulin, Sydney A.; Castaneda, Nicholas; Tetard, Laurene; Kang, Ellen H. (Frontiers in Soft Matter, 2025)
Gelsolin is a calcium (Ca2+) dependent, pH sensitive actin-binding protein that regulates actin filament dynamics to remodel the actin cytoskeleton. It is known that gelsolin binding induces conformational changes of actin filaments, leading to filament severing. However, the influence of physiological conditions, such as pH variations, on gelsolin-mediated filament severing activities, mechanics and conformations remains unclear despite their role in actin-actin interactions. Using Total Internal Reflection Fluorescence (TIRF) microscopy imaging and pyrene fluorescence assays, we demonstrate that filament severing efficiencies by gelsolin are enhanced in acidic conditions. In addition, analysis of filament thermal fluctuations using TIRF reveals that gelsolin binding stiffens actin filaments. Furthermore, we show that gelsolin binding induces conformational changes in filaments by measuring the filament half-pitch using high resolution Atomic Force Microscopy imaging. Together, our results suggest that pH modulation plays a key role in gelsolin-mediated filament severing activities, bending mechanics, and conformational changes, which have implications in many cellular processes including cell motility and morphogenesis.